Maternal death and the onward psychosocial circumstances of Australian Aboriginal children and young people - Zubrick, Stephen; Mitrou, F.; Lawrence, David; Silburn, Sven (Cambridge University Press, 2011)
This study sought to determine the social and emotional impact of maternal loss on Aboriginal children and young people using data from the Western Australian Aboriginal Child Health Survey (WAACHS). Data were from a population-based random sample of 5289 Aboriginal children aged under 18 years. Interview data about the children were gathered from primary carers and from their school teachers. Probabilistic record linkage to death registrations was used to ascertain deaths. Association between maternal death and subsequent psychosocial outcomes was assessed using univariate analyses and logistic regression. Of the 5289 Aboriginal children, 57 had experienced the death of their birth mother prior to the survey. Multi-variable adjustment accounting for age and gender found that, relative to children who were living with their birth mother, children whose birth mother had died were at higher risk for sniffing glue or other substances [odds ratio (OR) 3.4, 95% confidence interval (CI) 1.3–8.7], using other drugs (OR 2.8, 95% CI 1.2–6.8), talking about suicide (OR 2.6, 95% CI 1.2–5.7) and attempting suicide (OR 7.0, 95% CI 1.6–31.1). Although the death of a birth mother is relatively rare and the vast majority of Aboriginal children with adverse developmental outcomes live in families and are cared for by their birth mother, the findings here suggest that the loss of a birth mother and the circumstances arising from this impart a level of onward developmental risk for mental health morbidity in Australian Aboriginal children.